(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was carried out to chemically and microbiologicallyevaluate set yoghurt produced by two factories (F1 and F2) in KhartoumState. Ninety samples (45 from each factory) were collected andchemically and microbiologically analyzed at 1, 5 and 10 day intervals.The results showed that fat and total solids contents and titratable aciditywere higher in F2 than in F1, while protein and solids-non-fat contentswere higher in F1. Lacobacillus bulgaricus, coliform bacteria and yeastsand moulds counts were higher in F1. During storage, fat contentincreased in F1 and decreased in F2, while protein content increased in F1and followed an irregular pattern in F2. Total solids and solids-non-fatcontents increased till day 5, and then decreased at the end of the storageperiod in the two factories, while titratable acidity steadily increasedtowards the end in the two factories. Lactobacillus bulgaricus countincreased till day 5 then decreased towards the end in both factories,while coliform bacteria and yeasts and moulds counts increased towardsthe end.